Price Perception and Promotion on Honda Motorcycle Purchase Decision on CV. Various Motorcycles - Merry M. Pelupessy; Bin Raudha Arif Hanoeboen; Erly Leiwakabessy; Sancyes Henderina Pitna (ARRUS Journal of Social Sciences and Humanities, 2024)
Does Price Perception and Promotion affect Honda Motorcycle Purchase Decisions? Benefits of research For companies, this research is expected to help as well as contribute thoughts in strategies to increase sales volume. The method used in this study uses multiple linear regression analysis with the analysis tool used is SPSS version 26. This method is deliberately used to partially test and the coefficient of determination of the influence or not between variables. The number of samples from this study amounted to 106 respondents and the sample size was determined based on consideration using the hair formula (2010) The results of the study found that based on the results of analysis using the SPSS Program found that the variable X1 or Price Perception had a significant effect on the Purchase Decision of Honda Motorcycles because the sig value of 0.029 was smaller than 0.05 and t_calculate 2.212 ˃ t_table 1.984 and variable X2 or Promotion